2002
DOI: 10.1073/pnas.212516099
|View full text |Cite
|
Sign up to set email alerts
|

DBC2 , a candidate for a tumor suppressor gene involved in breast cancer

Abstract: A previously uncharacterized gene, DBC2 (deleted in breast cancer), was cloned from a homozygously deleted region at human chromosome 8p21. DBC2 contains a highly conserved RAS domain and two putative protein interacting domains. Our analyses indicate that DBC2 is the best candidate tumor suppressor gene from this region. It lies within the epicenter of the deletions and is homozygously deleted in 3.5% (7͞200) of breast tumors. Mutation analysis of DBC2 led to discovery of two instances of somatic missense mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
250
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(258 citation statements)
references
References 23 publications
6
250
1
1
Order By: Relevance
“…These deletions involve many genes that were earlier reported to be frequently lost by deletion, mutation or promoter methylation events in various solid tumours and acute leukaemia, such as ETV6 (12p13), SLIT2(4p15), AUTS2(7q11), NF1(17q12), MSH5 (6p21), MSH3(5q), HUS1(7p12), CDKN2D(19p13.2), WISP-1(8q24), IDE or TLX2(2p13.1). 14,[16][17][18][19][20][21][22][23][24] These genes are involved in major cellular processes, including DNA repair (MSH3, MSH5, HUS1), cell cycle regulation (HUS1, CDKN2D) and the RAS pathway (NF1). Another gene, IDE (10q32), a putative tumour suppressor insulin degrading enzyme, may play a role as a RB protector by preventing inactivation of RB1.…”
Section: Discussionmentioning
confidence: 99%
“…These deletions involve many genes that were earlier reported to be frequently lost by deletion, mutation or promoter methylation events in various solid tumours and acute leukaemia, such as ETV6 (12p13), SLIT2(4p15), AUTS2(7q11), NF1(17q12), MSH5 (6p21), MSH3(5q), HUS1(7p12), CDKN2D(19p13.2), WISP-1(8q24), IDE or TLX2(2p13.1). 14,[16][17][18][19][20][21][22][23][24] These genes are involved in major cellular processes, including DNA repair (MSH3, MSH5, HUS1), cell cycle regulation (HUS1, CDKN2D) and the RAS pathway (NF1). Another gene, IDE (10q32), a putative tumour suppressor insulin degrading enzyme, may play a role as a RB protector by preventing inactivation of RB1.…”
Section: Discussionmentioning
confidence: 99%
“…1b, Gi: 24432106). The DBC1 gene was initially identified as it is localized to a region of chromosome 8p21 that was homozygously deleted in human breast cancer; however, the molecular function of DBC1 is poorly understood 18,19 .To examine the interaction between endogenous DBC1 and SIRT1, cell extracts from human osteosarcoma U2OS cells were immunoprecipitated with the anti-SIRT1 antibody or with the …”
mentioning
confidence: 99%
“…1b, Gi: 24432106). The DBC1 gene was initially identified as it is localized to a region of chromosome 8p21 that was homozygously deleted in human breast cancer; however, the molecular function of DBC1 is poorly understood 18,19 .…”
mentioning
confidence: 99%
“…Many mutations, especially those involving recessive oncogenes, have been described in invasive lung carcinomas (Akita, 2004). Hamaguchi et al have found a novel tumor suppression gene named Deleted in Breast Cancer 2 (DBC2) in human chromosome 8p21, which belonged to the RhoBTB family (Hamaguchi et al, 2002). Recent researches indicate that DBC2 participates in diverse cellular activities, significantly influences cellcycle, apoptosis, cytoskeleton and membrane-trafficking pathways (Siripurapu et al, 2005;Chang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, DBC2 is isolated as a tumor suppressor gene from human chromosome 8p21, and it is the best candidate tumor suppressor gene from this region (Hamaguchi et al, 2002). Incidence of DBC2 losses has been detected in various carcinomas including prostate, breast, lung, colon, rectum, bladder, liver and larynx carcinoma (Emi et al, 1992;Lundgren et al, 1992;Bova et al, 1993;Fujiwara et al, 1993;Sunwoo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%